(a+b)^4-(a-b) ^4
use ncn formula
Answers
Answered by
8
Hello..... ☺
please refer to the attachment above.
..
thank you ☺
please refer to the attachment above.
..
thank you ☺
Attachments:
![](https://hi-static.z-dn.net/files/d6c/7386989fbd81cc3d59d916c71dd6c4a1.jpg)
NidhraNair:
I was only offline for 3days :(
Answered by
1
hey ur answer
(a+b)f-(a-b)⁴
(a+b)⁴
=⁴co a ²b°ca³b+c2a²b²+c⁴ab³+ca°b⁴
(a-b)⁴
=coa⁴b°-⁴c1a³b¹-⁴c2a²b²-⁴c3a²b³+⁴ca°b⁴^²
(a+b)f-(a-b)⁴
(a+b)⁴
=⁴co a ²b°ca³b+c2a²b²+c⁴ab³+ca°b⁴
(a-b)⁴
=coa⁴b°-⁴c1a³b¹-⁴c2a²b²-⁴c3a²b³+⁴ca°b⁴^²
Similar questions